Method for preparing graphene dispersion liquid by combining gemini surfactant with sanding process
Through the method of combining bimini surfactant and sand grinding process, the problem of graphene dispersion is solved, and the graphene dispersion is achieved with high efficiency dispersion and stability, which simplifies the processing technology and improves the application potential.
Patent Information
- Application Number
- CN202411742064.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to effectively disperse graphene, causing it to agglomerate in solution and affecting its application promotion.
The bimini surfactant combined with sand grinding technology is used to fully disperse graphene through predispersion and sand grinding, and the amphiphilic structure of the bimini surfactant interacts with the graphene surface to reduce surface tension and control particle size distribution.
The efficient dispersion and stability of graphene is achieved, the subsequent processing technology is simplified, and the stability and application potential of the dispersion liquid are significantly improved.
Smart Images

Figure BDA0005162797360000111 
Figure BDA0005162797360000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene, and in particular to a method for preparing a graphene dispersion by combining a gemini surfactant with a sand milling process. Background Art
[0002] Ideal graphene is a two-dimensional material with a single layer of carbon atoms, which is highly crystalline, has a high area ratio, an ultra-thin structure, and excellent electrical, optical, and thermal properties. However, graphene has an extremely high surface energy. In order to reduce this high surface energy, graphene sheets tend to get close to each other and stack together to form aggregates. At the same time, there are strong intermolecular forces between the graphene sheets, such as van der Waals forces. If the dispersant is not properly selected or the dispersion conditions are insufficient, the graphene will not be fully dispersed in the solution, and then agglomeration will occur.
[0003] At present, the dispersion of graphene has always been a key technical bottleneck restricting the promotion and application of graphene. For graphene, a more common dispersion method is physical dispersion, such as ① mechanical dispersion, including ball mills and sand mills, which break the interlayer van der Waals force by strong shearing and impacting the graphene to achieve dispersion. ② Ultrasonic dispersion, which generates high-energy vibrations through the cavitation effect to disperse graphene in the solution. ③ Microwave radiation, using the energy of microwave heating to disperse graphene in the solvent. Another dispersion method is chemical modification dispersion, such as ① covalent bond dispersion, which introduces functional groups such as hydroxyl and carboxyl groups by chemical reactions to improve the hydrophilicity and dispersibility of graphene, but may destroy the intrinsic structure of graphene. ② Non-covalent bond modification, which uses the π-π interaction or electrostatic interaction between surfactants and graphene sheets to achieve dispersion without destroying the intrinsic structure of graphene.
[0004] In order to maintain the consistency of the intrinsic structure and particle size distribution of graphene, mechanical dispersion is combined with non-covalent bond modification to prepare graphene dispersion. In mechanical dispersion, the sand mill has a high efficiency in dispersing graphene and can achieve precise control of the particle size. In non-covalent modification, if traditional surfactants are selected, their molecular structure is single, their surface activity is limited, their ability to reduce surface tension may be weak, their environmental adaptability is poor, and their application is limited. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a graphene dispersion by combining a gemini surfactant with a sand milling process.
[0006] The invention provides a method for preparing a graphene dispersion by combining a gemini surfactant with a sand milling process, comprising the following steps: adding graphene to a gemini surfactant solution for pre-dispersion, and sand milling the obtained graphene aqueous solution to obtain the graphene dispersion.
[0007] As a preferred technical solution of the present invention, the gemini surfactant includes one or more of an amide-based gemini quaternary ammonium salt gemini surfactant (GS-A6), a gemini nonionic surfactant wetting and leveling agent (104E) and a sulfonate gemini surfactant (YTY-18).
[0008] As a preferred technical solution of the present invention, in the gemini surfactant solution, the mass ratio of solute to solvent is (0.3-1.0):100.
[0009] The surface tension of the gemini surfactant solution is tested to determine the critical micelle concentration of the gemini surfactant, which provides a scientific basis for the use of the surfactant and helps to optimize the concentration of the surfactant, avoid waste and achieve the best effect.
[0010] As a preferred technical solution of the present invention, the mass ratio of the gemini surfactant to graphene is (0.3-1.0):2.5.
[0011] As a preferred technical solution of the present invention, before the pre-dispersion, the pH of the system is adjusted to 3-11.
[0012] If the pH is not adjusted to about 1-2, it is acidic. The change of pH will directly affect the potential of the particle surface in the slurry, thereby affecting the electrostatic interaction between particles. Before pre-dispersion, the pH of the system is adjusted to 3-11, and the electrostatic repulsion between particles is enhanced, which is beneficial to prevent particle agglomeration and improve the stability of the slurry.
[0013] As a preferred technical solution of the present invention, the pre-dispersion includes one or more combinations of magnetic stirring, paddle stirring and ultrasonic dispersion; the rotation speed of the magnetic stirring and paddle stirring is 600r / min, the frequency of the ultrasonic dispersion is 40kHz, and the pre-dispersion time is 2h.
[0014] Through pre-dispersion, graphene is fully soaked into the solution and there is no floating powder in the solution.
[0015] As a preferred technical solution of the present invention, the sand milling speed is 500 to 3000 r / min and the time is 10 to 120 min.
[0016] After sand grinding, the particle size of graphene reaches 0.5 to 5 μm.
[0017] The present invention also provides a graphene dispersion obtained according to the above method.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] Gemini surfactants have two hydrophobic chains, two hydrophilic groups, and one connecting group, which makes them more densely arranged at the interface, has lower surface energy, and has higher surface activity. They can significantly reduce the surface tension of the liquid and can be combined with the sand milling process to prepare graphene dispersions with high dispersion stability.
[0020] In the preparation of the graphene dispersion of the present invention, the unique amphiphilic structure of the Gemini surfactant enables it to interact with the graphene surface and the dispersion medium more effectively, the hydrophilic group has good compatibility with water molecules, and the hydrophobic group can attract the non-polar surface of the graphene, thereby enhancing the stability of the graphene in the dispersion medium. Secondly, the sand grinding process can make the graphene fully contact with the Gemini surfactant and can control the particle size distribution of the graphene to a certain extent.
[0021] The method of the present invention can achieve efficient dispersion of graphene with good stability. The entire preparation process is green, safe and environmentally friendly. At the same time, the subsequent processing technology of the material is significantly simplified. The gemini surfactant can provide strong support for the further processing and application of graphene, and has important practical significance and industrialization potential. DETAILED DESCRIPTION
[0022] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0023] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0027] The method for preparing a graphene dispersion by combining a gemini surfactant with a sand milling process comprises the following steps: adding graphene to a gemini surfactant solution for pre-dispersion, and sand milling the obtained graphene aqueous solution to obtain a graphene dispersion.
[0028] In some embodiments, the gemini surfactant is GS-A6, 104E, or YTY-18.
[0029] In some embodiments, in the gemini surfactant solution, the mass ratio of solute to solvent is (0.3-1.0):100.
[0030] In some preferred embodiments, the solvent water is 100 parts by weight, and the solute gemini surfactant is 0.40, 0.45, 0.48, 0.50, 0.55 and 0.60 parts by weight.
[0031] In some embodiments, the mass ratio of the gemini surfactant to graphene is (0.3-1.0):2.5.
[0032] In some preferred embodiments, the graphene is 2.5 parts by weight, and the gemini surfactant is 0.40, 0.45, 0.48, 0.50, 0.55 and 0.60 parts by weight.
[0033] In some embodiments, the pH of the system is adjusted to 3-11 before pre-dispersion.
[0034] In some preferred embodiments, the pH of the system is adjusted to 3, 7, 8, 9, 10, or 11 before pre-dispersion.
[0035] In some embodiments, pre-dispersion includes one or more combinations of magnetic stirring, paddle stirring and ultrasonic dispersion; the rotation speed of magnetic stirring and paddle stirring is 600r / min, the frequency of ultrasonic dispersion is 40kHz, and the pre-dispersion time is 2h.
[0036] In some embodiments, the sanding speed is 500-3000 r / min, and the time is 10-120 min.
[0037] In some preferred embodiments, the sanding speed is 1200 r / min, time 90 min; 2400 r / min, time 50 min; 2000 r / min, time 60 min; 1000 r / min, time 100 min; 2500 r / min, time 40 min; 2400 r / min, time 80 min.
[0038] The present invention also provides a graphene dispersion obtained according to the method.
[0039] In the following examples and comparative examples, the GS-A6, 104E and YTY-18 used are all commercially available and are not particularly limited. The description will not be repeated below.
[0040] Example 1
[0041] The graphene dispersion is prepared by using a Gemini surfactant combined with a sand milling process, and the steps are as follows:
[0042] First, 100 parts of water were taken as solvent, 0.48 parts of 104E were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was 62.4 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 10, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 1200r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size distribution reaches the ideal value, the required time is 90min.
[0043] The viscosity of the graphene dispersion after sand grinding was tested to be 856 Pa·s; the graphene dispersion after sand grinding was centrifuged at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water, ultrasonicated for 15 min, and the absorbance was tested at 241.6 nm to be 0.078 A; 50 μL of the graphene dispersion after sand grinding was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -38.9 mV; the particle size D50 was 2.48 μm.
[0044] It can be seen from this embodiment that, by weight, when 100 parts of water are taken as the solvent, 0.48 parts of the Gemini surfactant are added, and the speed and sanding time of the sand mill are set to 1200 r / min and 90 min, respectively, a graphene dispersion with good stability is prepared, the viscosity is 856 Pa·s, the Zeta potential at pH=10 is -38.9 mV, and the particle size D50 is 2.48 μm.
[0045] Example 2
[0046] The graphene dispersion is prepared by using a Gemini surfactant combined with a sand milling process, and the steps are as follows:
[0047] First, 100 parts of water were taken as solvent, 0.50 parts of 104E were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 59.1 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 10, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2400r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size distribution reaches the ideal value, the required time is 50min. The viscosity of the graphene dispersion after sand grinding was tested to be 850 Pa·s; after centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water, ultrasonicated for 15 min, and the absorbance at 241.6 nm was tested to be 0.093 A; 50 μL of the graphene dispersion after sand grinding was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -39.3 mV; the particle size D50 was 2.41 μm.
[0048] It can be seen from this example that, by weight, when 100 parts of water is taken as solvent and 0.50 parts of Gemini surfactant is added, the surface tension of the aqueous solution is 59.1 mN·m -1 During the experiment, when the gemini surfactant 104E was this number, the tested surface tension was the lowest value. Therefore, this number was selected as the critical micelle concentration of the gemini surfactant. When the speed and sand milling time were set to 2400r / min and 50min respectively, a graphene dispersion with good stability was prepared, with a viscosity of 850Pa·s, a Zeta potential of -39.3mV at pH=10, and a particle size D50 of 2.41μm.
[0049] Determining the critical micelle concentration can provide a scientific basis for the use of this surfactant; secondly, it can help optimize the concentration of the surfactant, avoid waste and achieve the best effect.
[0050] Example 3
[0051] The graphene dispersion is prepared by using a Gemini surfactant combined with a sand milling process, and the steps are as follows:
[0052] First, 100 parts of water were taken as solvent, 0.55 parts of 104E were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was 59.3 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 8, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2000r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size distribution reaches the ideal value, the required time is 60min.
[0053] The viscosity of the dispersion after sand grinding was tested to be 832 Pa·s; after centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water, ultrasonicated for 15 min, and the absorbance at 241.6 nm was tested to be 0.085 A; 50 μL of the graphene dispersion after sand grinding was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -36.8 mV; the particle size D50 was 2.59 μm.
[0054] It can be seen from this embodiment that, by weight, when 100 parts of water are taken as the solvent and 0.55 parts of the Gemini surfactant are added, the speed of the sand mill and the sand milling time are set to 2000 r / min and 60 min, respectively, a graphene dispersion with good dispersion is prepared, the viscosity is 832 Pa·s, the Zeta potential at pH=10 is -36.8 mV, and the particle size D50 is 2.59 μm.
[0055] Example 4
[0056] The method for preparing graphene dispersion by using a gemini surfactant combined with a sand milling process comprises the following steps:
[0057] First, 100 parts of water were taken as solvent, 0.60 parts of 104E were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was 67.2 mN·m -1, add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 9, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 1000r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size is evenly distributed to the ideal value, the required time is 100min.
[0058] The viscosity of the dispersion after sand milling was tested to be 799 Pa·s; after centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water, ultrasonicated for 15 min, and the absorbance at 241.6 nm was tested to be 0.082 A; 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -35.8 mV; the particle size D50 was 2.37 μm.
[0059] It can be seen from this example that, by weight, when 100 parts of water is taken as solvent and 0.60 parts of Gemini surfactant is added, the surface tension of the aqueous solution is 67.2 mN·m -1 When the speed and sanding time of the sand mill were set to 1000 r / min and 100 min respectively, a graphene dispersion with good stability was prepared, with a viscosity of 799 Pa·s, a Zeta potential of -35.8 mV at pH = 10, and a particle size D50 of 2.37 μm.
[0060] Example 5
[0061] The method for preparing graphene dispersion by using a gemini surfactant combined with a sand milling process comprises the following steps:
[0062] First, 100 parts of water were taken as solvent, 0.40 parts of GS-A6 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 48.5 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 11, and use magnetic stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2500r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size distribution reaches the ideal value, the required time is 40min.
[0063] The viscosity of the dispersion after sand milling was tested to be 754 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.091 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -39.0 mV. The particle size D50 was 1.99 μm.
[0064] It can be seen from this example that, by weight, when 100 parts of water is taken as solvent and 0.40 parts of Gemini surfactant is added, the surface tension of the aqueous solution is 48.5 mN·m -1 In the experiment, when the surfactant GS-A6 was used for this portion, the tested surface tension was the lowest value. Therefore, this portion was selected as the critical micelle concentration of the gemini surfactant. When the speed and sand milling time were set to 2500r / min and 40min respectively, a graphene dispersion with good stability was prepared, with a viscosity of 754Pa·s, a Zeta potential of -39.0mV at pH=10, and a particle size D50 of 1.99μm.
[0065] Example 6
[0066] The method for preparing graphene dispersion by using a gemini surfactant combined with a sand milling process comprises the following steps:
[0067] First, 100 parts of water were taken as solvent, 0.45 parts of Gemini surfactant YTY-18 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 62.6 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 10, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add zirconia beads with a diameter of 1.0mm to the sand mill. The filling amount of zirconia beads is 75% of the volume of the sand mill grinding barrel. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2400r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size distribution reaches the ideal value, the required time is 80min.
[0068] The viscosity of the dispersion after sand milling was tested to be 800 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.093 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -37.8 mV. The particle size D50 was 1.88 μm.
[0069] It can be seen from this example that, by weight, when 100 parts of water is taken as solvent and 0.45 parts of Gemini surfactant is added, the surface tension of the aqueous solution is 62.6 mN·m -1 During the experiment, when the surfactant YTY-18 was this portion, the tested surface tension was the lowest value. Therefore, this portion was selected as the critical micelle concentration of the gemini surfactant. When the speed and sand mill time were set to 2400r / min and 80min respectively, a graphene dispersion with good stability was prepared with a viscosity of 800Pa·s, a Zeta potential of -37.8mV at pH=10, and a particle size D50 of 1.88μm.
[0070] Example 7
[0071] Same as Example 6, except that, before pre-dispersion, the pH of the system was adjusted to 3, as follows:
[0072] First, 100 parts of water were taken as solvent, 0.45 parts of YTY-18 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 62.6 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 3, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add 75% of zirconia beads with a diameter of 1.0mm to the sand mill. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2400r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size is evenly distributed to the ideal value, the required time is 80min.
[0073] The viscosity of the dispersion after sand milling was tested to be 950 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.070 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be 2.58 mV. The particle size D50 was 2.51 μm.
[0074] Example 8
[0075] Same as Example 6, except that, before pre-dispersion, the pH of the system was adjusted to 7, as follows:
[0076] First, 100 parts of water were taken as solvent, 0.45 parts of YTY-18 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 62.6 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 7, and use paddle stirring for pre-dispersion. The stirring speed is 600r / min for 2h. Add 75% of zirconia beads with a diameter of 1.0mm to the sand mill. After turning on the chiller of the sand mill, turn on the pump and compressor. The equipment tank temperature can be started only when it feels cool when it cools down. Set the sand mill speed to 2400r / min. Start adding materials after the sand mill runs stably. Adjust the diaphragm pump to control the slurry flow rate to make the slurry circulate and grind. When the particle size is evenly distributed to the ideal value, the required time is 80min.
[0077] The viscosity of the dispersion after sand milling was tested to be 842 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.080 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -25.2 mV. The particle size D50 was 2.38 μm.
[0078] By comparing Examples 7 to 8 with Example 6, it can be seen that if the pH is adjusted to 3 or 7 before pre-dispersion, the absolute value of the Zeta potential of the final dispersion will be lower, the viscosity will increase, and coagulation will be more likely to occur. Therefore, it is better to adjust the system pH to 8 to 11 before pre-dispersion.
[0079] Comparative Example 1
[0080] The same as Example 6, except that the pH is not adjusted before pre-dispersion, as follows:
[0081] First, 100 parts of water were taken as solvent, 0.45 parts of YTY-18 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 62.6 mN·m -1, add 2.5 parts of graphene to the aqueous solution, measure the pH of the system to be 1.5, use paddle stirring for pre-dispersion, stirring speed is 600r / min, time is 2h, add 75% of zirconia beads with a diameter of 1.0mm to the sand mill, turn on the chiller of the sand mill, turn on the pump and compressor, and start the equipment tank when it feels cool when it cools down. Set the sand mill speed to 2400r / min, start feeding after the sand mill runs stably, adjust the diaphragm pump to control the slurry flow rate, and make the slurry circulate and grind. When the particle size is evenly distributed and reaches the ideal value, the required time is 80min. (The sand mill speed setting and the diaphragm pump control flow rate are both to improve the grinding effect, and the time to reach the ideal particle size is 80min).
[0082] The viscosity of the dispersion after sand milling was tested to be 1005 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.060 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be 2.42 mV. The particle size D50 was 2.68 μm.
[0083] It can be seen from this comparative example that if the pH of the system is not adjusted before pre-dispersion, the viscosity of the final graphene dispersion will increase more, the stability of the absorbance of the conductive slurry will decrease, and the absolute value of the Zeta potential will also decrease, which shows that adjusting the appropriate pH value is necessary for the preparation of the conductive slurry.
[0084] Comparative Example 2
[0085] Same as Example 6, except that no pre-dispersion is performed, as follows:
[0086] First, 100 parts of water were taken as solvent, 0.45 parts of YTY-18 were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 62.6 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 10, add 75% of zirconia beads with a diameter of 1.0mm to the sand mill, turn on the chiller of the sand mill, turn on the pump and compressor, and start the equipment when the tank temperature cools down and feels cold. Set the sand mill speed to 2400r / min, start adding materials after the sand mill runs stably, adjust the diaphragm pump to control the slurry flow rate, and make the slurry circulate and grind. When the particle size is evenly distributed and reaches the ideal value, it takes 100min. (The speed setting of the sand mill and the flow rate controlled by the diaphragm pump are both to improve the grinding effect, and the time to reach the ideal particle size is 100min).
[0087] The viscosity of the dispersion after sand milling was tested to be 815 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.068 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -30.2 mV. The particle size D50 was 2.35 μm.
[0088] It can be seen from this comparative example that if pre-dispersion is not performed, the grinding time of the final graphene dispersion will increase, the stability of the absorbance of the conductive slurry will decrease, and the absolute value of the Zeta potential will also decrease, which shows that pre-dispersion is necessary for the preparation of the conductive slurry.
[0089] Comparative Example 3
[0090] Same as Example 6, except that the "gemini surfactant" is replaced by the traditional surfactant "sodium dodecyl sulfate" in non-covalent bond modification, as follows:
[0091] First, 100 parts of water were taken as solvent, 0.45 parts of sodium dodecyl sulfate were added, and ultrasonic dispersion was performed to obtain a uniform aqueous solution. The surface tension was tested to be 70.2 mN·m -1 , add 2.5 parts of graphene to the aqueous solution, adjust the pH of the system to 10, and use paddle stirring for pre-dispersion, the stirring speed is 600r / min, the time is 2h, add 75% of zirconia beads with a diameter of 1.0mm to the sand mill, turn on the chiller of the sand mill, turn on the pump and compressor, and start the equipment tank when it feels cool when it cools down. Set the sand mill speed to 2400r / min, start adding materials after the sand mill runs stably, adjust the diaphragm pump to control the slurry flow rate, and make the slurry circulate and grind. When the particle size is evenly distributed and reaches the ideal value, the required time is 80min. (The sand mill speed setting and the diaphragm pump control flow rate are both to improve the grinding effect, and the time to reach the ideal particle size is 80min).
[0092] The viscosity of the dispersion after sand milling was tested to be 980 Pa·s. After centrifugation at 5000 rpm for 5 min, 50 μL of the slurry after centrifugation was diluted in 50 mL of water and ultrasonicated for 15 min. The absorbance at 241.6 nm was tested to be 0.065 A. 50 μL of the dispersion after sand milling was diluted in 50 mL of water, the pH was adjusted to 10, and the Zeta potential was tested to be -26.3 mV. The particle size D50 was 2.54 μm.
[0093] It can be seen from this comparative example that if the gemini surfactant is replaced by the traditional surfactant in the non-covalent modification, the ability to reduce the surface tension of the aqueous solution is weakened, and at the same time, the viscosity increase of the conductive paste increases, the stability of the absorbance decreases, and the absolute value of the Zeta potential value also decreases, which shows that the selection of gemini surfactants with special structures is necessary for the preparation of conductive pastes.
[0094] The graphene dispersions prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were placed at room temperature (23° C.) for 3 months, and then their viscosity was tested. The absorbance was tested at 241.6 nm after centrifugal dilution. The pH of the dispersions was adjusted to 10 after dilution, and the Zeta potential and particle size D50 were tested. The results are shown in Table 1.
[0095] Table 1 Performance test data of graphene dispersion after being placed at room temperature for 3 months
[0096]
[0097]
[0098] It can be seen from the performance test data in Table 1 that the graphene dispersions prepared in Examples 1 to 8 have stable performance and remain in good condition after being placed for 3 months, and it is observed that no stratification and particle sedimentation occur. However, the graphene dispersions prepared in Comparative Examples 1 to 3 have serious graphene agglomeration after being placed for three months, and the viscosity increases greatly. It is also observed that the system is close to a stratified state, resulting in a decrease in absorbance, a decrease in the absolute value of zeta potential, and a significant increase in the adsorption between particles in the dispersion, resulting in particle sedimentation.
[0099] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a graphene dispersion using a gemini surfactant combined with a sand milling process, characterized in that: The following steps are involved: Graphene is added to the gemini surfactant solution for pre-dispersion, and the obtained graphene aqueous solution is sand-milled to obtain the graphene dispersion.
2. The method according to claim 1, characterized in that: The gemini surfactant includes one or more of an amide-based gemini quaternary ammonium salt gemini surfactant, a gemini nonionic surfactant wetting and leveling agent, and a sulfonate gemini surfactant.
3. The method according to claim 1, characterized in that In the gemini surfactant solution, the mass ratio of solute to solvent is (0.3-1.0):
100.
4. The method according to claim 1, characterized in that: The mass ratio of the gemini surfactant to graphene is (0.3-1.0):2.
5.
5. The method according to claim 1, characterized in that Before the pre-dispersion, the pH of the system is adjusted to 3-11.
6. The method according to claim 1, characterized in that The pre-dispersion includes one or more combinations of magnetic stirring, paddle stirring and ultrasonic dispersion; the rotation speed of the magnetic stirring and paddle stirring is 600r / min, the frequency of the ultrasonic dispersion is 40kHz, and the pre-dispersion time is 2h.
7. The method according to claim 1, characterized in that The sand milling speed is 500-3000 r / min, and the time is 10-120 min.
8. A graphene dispersion obtained by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Star-shaped carboxylic group amphoteric ion surfactant as well as preparation method and application thereof
CN108440322A
Graphene dispersion liquid and preparation method thereof, and anticorrosive paint using graphene dispersion liquid
CN111303676A
Preparation method of graphene-containing easily-dispersed phthalocyanine blue pigment
CN116478558A
Method for producing multilayer graphene coated substrate
WO2012108371A1
Cited By
High-solid-content graphene oxide slurry, viscosity reducer, graphene film and preparation method
CN121494554A